Reading with the senses in Victorian literature and science - Coombs, David Sweeney, 1977- (University of Virginia Press, 2019)
"Reading with the Senses shows how major Victorian novelists, aesthetes, and scientists dramatically revised their understanding of reading and sensory perception in light of nineteenth-century scientific work in psychology, physiology, and physics. This book argues that the rise of perception science led major Victorian writers--George Eliot, Thomas Hardy, Vernon Lee, and Walter Pater--to embrace a radical literary empiricism that had transformative effects on the novel and the Aesthetic Movement. Coombs shows how the effects of this radical literary empiricism continue to reverberate in our own moment, when a descriptive turn in the humanities has pushed literary critics to align their reading practices with scientific methods of observation"--